Sistem pendukung Keputusan Penerimaan Karyawan Menggunakan Algoritma Multifactor Evaluation Process (Studi Kasus: XYZ Department Store Regional Priangan Timur) - Lia Amelia (Universitas Ivet, 2021)
The management of human resources in a company affects many aspects that determine the success of the company. One of the efforts made is the selection of employees. Based on the interview results, XYZ Depstore in the process of recruiting employees is carried out regionally and is still carried out manually with the weight of the criteria that have not been detailed, this raises several problems including requiring a lot of time, the occurrence of human errors which cause unfair and inaccurate calculations. So that we need a system with a certain algorithm that automatically ranks prospective employees with accuracy, fairness and faster among the many applicants. In developing the system, the Multifactor Evaluation Process (MFEP) algorithm is used with three criteria and its weights that have been determined, namely 20% document, 10% psychological test and 70% interview. The system development method used is extreme programming. The system generates a sequence of recommendations for candidate employees who deserve to be accepted to help the company make decisions. Also equipped with features for prospective employees to submit application documents and personal data online, job vacancies information, selection announcements and report generation. Functional testing of the system is carried out using the black box method, showing the results of all the scenarios that have been made. The results of the calculation on the system are compared with the results of calculations on Microsoft Excel using 30 alternative prospective employees, showing the same calculation results, so that the accuracy rate is 100%.